A Comparative Study of Conventional vs. Endoscopic Septoplasty - Bhagyesh Lalitchandra Darji (National Board of Examinations Journal of Medical Sciences)
Background: Septoplasty is the treatment for the symptomatic Deviated Nasal Septum. There has been a drift from septal resection to mucosal preservation to conservation of possible septal framework in the septoplasty surgeries. The endoscopic technique is modern evolution of the septoplasty surgery. This study has been undertaken to evaluate the conventional and endoscopic approaches of the septoplasty surgeries and aid in statistical informative data to ongoing researches for better outcome comparison. Aims and Objectives: To compare conventional and endoscopic techniques of Septoplasty and to find out which technique is better on the basis of various intraoperative and postoperative objectives. Material and Methods: A prospective randomized comparative study was conducted with a sample size of total 60 patients; 30 in each group. Both the groups were statistically compared for various predefined intraoperative and postoperative objective to determine the better technique of septoplasty. Results: Endoscopic technique was better than conventional in terms of ease for surgical process, time taken for the surgery, intra operative blood loss, visualization of the pathology and postoperative residual deviation. Conclusions: Endoscopic technique was found better in terms of less intra operative complication like bleeding, better visualization, better illumination, magnification, more conservative approach, ease of surgery, less time duration of surgery and less postoperative residual deviation with limitation of binocular vision and bimanual work. Endoscopic septoplasty is modern alternative technique to conventional septoplasty and is a good teaching tool also.